(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Expression of quantitative links through wordformative categories, which are defined as totality of wordformative meanings, expressed by means of affixation, are obligatory in languages with developed wordformative system.In Russian, wordformative categories of the nouns are connected with conceptual category of a quantity, which supplement the number or are cuted with it. First of all, these are wordformative categories of singleness of occurrence, wordformative categories of the collective noun, wordformative categories of adultness, and also wordformative categories of subjective appraisal, uniting three parts of speech (noun, adjective, adverb).